Efficiency of potato peel extract in the preservation of cow butter - Lemlem Tadesse Teklehaymanot; Talbachew Tadesse Nadew; Abebe Teshome Ayele (Heliyon)
This study investigates that the phenolic compound extracted from the potato peels using ethanol by maceration as a natural preservation agent for cow butter, yielding 10.42 ± 0.03 % phenolic compound. A quantitative and qualitative analysis of potato peels extract (PPE) was conducted to examine the phenolic compounds. The major preliminary phytochemical screenings (Alkaline Reagent Test, Ferric Chloride Test, Chloride Test) were performed to detect the presence of phenols, flavonoids, and tannins. The total phenolic content was measured using the Folin–Ciocalteu method with UV spectrophotometry, which produced 2.9468 ± 0.03 mg GAE/g of dry extract. The total flavonoid content was determined using the aluminum chloride colorimetric method, resulting in 3.6885 ± 0.02 mg equivalent Quercetin/g of dry extract. During 21 days, butter samples treated with PPE at various concentrations (0.2 % and 0.3 %) and storage temperatures (20 °C and 45 °C) were examined for chemical parameters (peroxide value and free fatty acid value) and microbiological parameters (aerobic total bacterial count and yeast mould count). The findings showed that the samples preserved at 20 °C with a concentration of 0.3 % extract had better preservation than samples stored at other temperatures. It also showed lower values of peroxide and free fatty acids, as well as less microbial growth. On the other hand, samples without extract that were kept at 45 °C demonstrated more oxidation and microbial growth. The oxidative stability of cow butter was assessed using the Rancimat method. Results indicate that PPE significantly enhances both oxidative stability and shelf life, offering preservative benefits for up to six months. Specifically, the induction period (IP) at room temperature reached 3960 h (165 days) with PPE, compared to only 120 h (5 days) without it. These findings suggest that the phenolic compounds in the potato peels could serve as natural preservatives for cow butter, particularly when stored at lower temperatures.